The role of Producer Organisations in the vegetable value chain: an application to the red chicory from Veneto - Nucera, Maria; Ferrari, Giovanna Maria; Finizia, Antonella; Merciai, Stefano; Sorrentino, Alessandro (Italian Review of Agricultural Economics, 2016)
This paper is about agricultural value chain and aims at evaluating the impact of Producer Organizations (POs) on a vegetable value chain. In particular, the objective of this study is to compare added value distribution among players in the vegetable sectors in different supply chain scenarios, i.e. supply chain with a PO as intermediary and supply chain with a wholesaler as intermediary. We will focus on an empirical application of ISMEA value chain to the supply chain of two vegetables: the “Radicchio rosso di Treviso tardivo IGP” and its equivalent not certified product, the “spadone” chicory, which are both produced in the Veneto region only. The case study evidence suggests that POs allow farmers to reach a greater benefit, compared to ordinary supply chain, even if such efficiencies could have been higher. Since the substantial review and reduction of direct support to agricultural income, the tools improving supply concentration appear as the few tools, which can enable a return to profitability, as well as efficiency of the supply chains themselves.